Lipostatic Mechanisms Preserving Cerebellar Lipids in MPTP-Treated Mice: Focus on Membrane Microdomains and Lipid-Related Gene Expression - Díaz, Mario; Luis-Amaro, Ana Canerina; Rodriguez Barreto, Deiene; Casañas-Sánchez, Verónica; Pérez, José A.; Marin, Raquel (Frontiers in Molecular Neuroscience, 2019)
The cerebellum is an essential component in the control of motor patterns. Despite dramatic alteration of basal ganglia morpho-functionality in Parkinson’s disease (PD), cerebellar function appears to be unaffected by the disease. Only recently this brain structure has been proposed to play compensatory roles in PD-induced motor dysfunction, particularly during the initial asymptomatic stages of PD. In PD subjects and animal models of Parkinson’s disease, such the MPTP-treated mice, brain structures other than basal ganglia are also affected by the disease, including cortical areas not involved in motor control. Thus, it is noteworthy that the cerebellum remains unaffected. In the present study, we have analysed the lipid composition of membrane microdomains (lipid rafts and non-raft domains) and assessed the expression levels of genes encoding for the synthesis of membrane-related lipids. The outcomes revealed that membrane domain lipids in cerebellum are highly preserved both in control and MPTP-treated mice as compared to control animals. Likewise, only small, mostly not significant, changes were observed in the expression of lipid-related genes in the cerebellum. Indeed, most changes were related to aging rather than to the exposure to the neurotoxin. Conversely, in the same animals, lipid composition and gene expression were dramatically altered in the occipital cortex, a brain area unrelated to the control of motor function. Immunohistochemistry of both brain areas revealed that the dopamine transporter (DAT) was expressed in occipital cortex but not in the cerebellum, as did DAT mRNAs. As MPTP neurotoxicity requires the expression of dopamine transporter to access intracellular compartments, we hypothesized that the absence of DAT in cerebellum hampers MPTP-induced toxicity. We conclude that cerebellum is endowed with efficient mechanisms to preserve nerve cell lipid homeostasis, which greatly maintain the stability of membrane microdomains involved in synaptic transmission, signal transduction and intercellular communication, which together may participate in the compensatory role of cerebellum in PD symptomatology.